Pre-Clinical Investigation of Keratose as an Excipient of Drug Coated Balloons - Emily Goel; Megan Erwin; Claire V. Cawthon; Carson Schaff; Nathaniel Fedor; Trevor Rayl; Onree Wilson; Uwe Christians; Thomas C. Register; Randolph L. Geary; Justin Saul; Saami K. Yazdani (Molecules, 2020)
Background: Drug-coated balloons (DCBs), which deliver anti-proliferative drugs with the aid of excipients, have emerged as a new endovascular therapy for the treatment of peripheral arterial disease. In this study, we evaluated the use of keratose (KOS) as a novel DCB-coating excipient to deliver and retain paclitaxel. Methods: A custom coating method was developed to deposit KOS and paclitaxel on uncoated angioplasty balloons. The retention of the KOS-paclitaxel coating, in comparison to a commercially available DCB, was evaluated using a novel vascular-motion simulating ex vivo flow model at 1 h and 3 days. Additionally, the locoregional biological response of the KOS-paclitaxel coating was evaluated in a rabbit ilio-femoral injury model at 14 days. Results: The KOS coating exhibited greater retention of the paclitaxel at 3 days under pulsatile conditions with vascular motion as compared to the commercially available DCB (14.89 ± 4.12 ng/mg vs. 0.60 ± 0.26 ng/mg, p = 0.018). Histological analysis of the KOS–paclitaxel-treated arteries demonstrated a significant reduction in neointimal thickness as compared to the uncoated balloons, KOS-only balloon and paclitaxel-only balloon. Conclusions: The ability to enhance drug delivery and retention in targeted arterial segments can ultimately improve clinical peripheral endovascular outcomes.